Ultrasound First for Removal of Nonpalpable Contraceptive Implants. (24th October 2020) - Herzog, Jackson; Walker, Lisa; Sutter, Christopher; Azar, Nami; Nakamoto, Dean
Abstract : The Sound Judgment Series consists of invited articles highlighting the clinical value of using ultrasound first in specific clinical diagnoses where ultrasound has shown comparative or superior value. The series is meant to serve as an educational tool for medical and sonography students and clinical practitioners and may help integrate ultrasound into clinical practice.